The Prevalence and Risk Factors for Preterm Delivery in Tehran, Iran - Najmeh Tehranian; Minoo Ranjbar; Fatemeh Shobeiri (Mashhad University of Medical Sciences, 2016)
Background & aim: Preterm delivery is one of the most important problems in pregnancy, as it is the primary cause of 75% of prenatal mortality and morbidities. This study aimed to determine the prevalence and risk factors for preterm delivery in Tehran, Iran. Methods:In this cross-sectional study performed in eight random hospitals from five different regions of Tehran (North, South, West, East, and center), the prevalence of preterm delivery was evaluated and the most frequent risk factors were identified. Samples were divided into preterm delivery (n=140) and term delivery (n=100) groups. Questionnaires were completed through interviews with mothers and using patient records. To analyze the data, Chi-square test was run, using SPSS version 16. Results: About 13,281 deliveries were included in the study. The highest and lowest prevalence of preterm delivery were 6.30% and 0.77% in the North and East regions of Tehran, respectively.  The overall prevalence of preterm delivery was 1.52% in Tehran. In the preterm group, age ≥35 years, pre-mature rupture of membranes, bleeding, gestational hypertension, history of preterm delivery and abortion, multiple pregnancy, and preeclampsia were significantly more frequent than the term delivery group. Conclusion: Spontaneous preterm birth was one of the major causes of maternal and neonatal morbidity; therefore, identification of its risk factors would be beneficial.